2010
DOI: 10.1016/j.solener.2010.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of different data averaging times on statistical analysis of distributed domestic photovoltaic systems

Abstract: The trend of increasing application of distributed generation with solar photovoltaics (PV-DG) suggests that a widespread integration in existing low-voltage (LV) grids is possible in the future. With massive integration in LV grids, a major concern is the possible negative impacts of excess power injection from on-site generation. For power-ow simulations of such grid impacts, an important consideration is the time resolution of demand and generation data. This paper investigates the impact of time averaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 11 publications
1
23
0
2
Order By: Relevance
“…These differences are higher for minimum values (up to 63%), delivered energy, than for the maximum values (up to 15%), exported energy. These results are consistent with previous findings showing that averaging has higher impacts on delivered than exported energy [25]. The explanation for this is that for PV power generation the fluctuations are deviations (due to cloud movements) from a well-defined maximum clear-sky radiation.…”
Section: Grid Citizenship Toolsupporting
confidence: 92%
See 1 more Smart Citation
“…These differences are higher for minimum values (up to 63%), delivered energy, than for the maximum values (up to 15%), exported energy. These results are consistent with previous findings showing that averaging has higher impacts on delivered than exported energy [25]. The explanation for this is that for PV power generation the fluctuations are deviations (due to cloud movements) from a well-defined maximum clear-sky radiation.…”
Section: Grid Citizenship Toolsupporting
confidence: 92%
“…Averaging move these high peaks closer to the base load. The results in [25] also shows that despite high impacts of averaging on individual building loads, the impacts on the aggregate load of a building cluster are lower (mainly for net delivered power), since random coincidence smoothens the load. It was found that in simulations of a distribution grid, the simulated voltage levels were robust to averaging of individual load profiles since the voltages depend mainly on the total power flow, to which a big cluster of buildings contributes.…”
Section: Grid Citizenship Toolmentioning
confidence: 87%
“…La revisión de áreas construidas se concentra usualmente en la capacidad de recolección solar de las cubiertas de edifi cios, estimando magnitudes generales por sectores (Izquierdo, 2008), aunque sin considerar fachadas o patios, como tampoco la estructura urbana. Una revisión más detallada del potencial solar de las edifi caciones requiere la información volumétrica de las construcciones y el cálculo de radiación recibida por cada frente o lugares anexos, que luego se puede grafi car e implementar en sistemas catastrales (UPM & POLIS, 2010). En un reciente proyecto de investigación desarrollado en Europa, se evaluó el potencial solar en tres ciudades: Lisboa, París y Vitoria-Gateiz.…”
Section: Catastros Energéticos Y Captación Solar Urbanaunclassified
“…La captación de energía solar para consumo directo en el lugar (on-site), permite prescindir de redes de transporte y distribución, evita la construcción, mantención y contaminación espacial de grandes sistemas (Widén, 2010). El presente estudio pretende entonces promover la aplicación de energías renovables en las ciudades, específi camente en el uso residencial, determinando la zonificación de sus requerimientos y posibilidades de captación solar.…”
unclassified
“…Between all the different alternatives, those modeling techniques that provide a high-temporal resolution are regarded as the most suitable ones due to the random nature of the end users' consumption and the renewable sources [12,13].…”
Section: Introductionmentioning
confidence: 99%